TINJAUAN HUKUM TERHADAP AKTA JUAL BELI YANG DIBUAT SECARA TIDAK SAH (Studi Putusan No.5/Pdt.G/2023/PN.Btl) - Nisa Parninda (PT. Hasba Edukasi Mandiri, 2025)
Land as a limited resource has multifunctional roles that create complexity in Indonesia's land law system, particularly regarding the validity of Property Sale and Purchase Deeds (AJB). This research aims to analyze the validity of AJB created by PPAT and identify legal protection mechanisms for land rights holders based on Decision Number 5/Pdt.G/2023/PN.Btl. The research method uses a normative juridical approach type with descriptive-analytical characteristics, utilizing secondary data in the form of primary, secondary, and tertiary legal materials analyzed qualitatively using deductive methods. The results show that AJB created by PPAT Agustinus Janarko Sigit Prasetio and Ratnawati contains legal defects due to non-compliance with cash, transparent, and real principles, as well as defective consent involving fraud and abuse of circumstances. The court provided repressive legal protection by canceling the deed and returning ownership rights to the original owner. The research concludes the importance of applying prudential principles in deed creation and the need to strengthen supervision systems to prevent harmful practices in land transactions.